Prevalence of needle stick injuries among nursing students from school of Health Sciences Universiti Sains Malaysia - Ibrahim, Nor Akmal Masor (Universiti Sains Malaysia, 2009)
Nursing students face the threat of needle stick injuries (NSIs) with the consequent risk of acquiring blood borne infections during their clinical training. The aim of this cross sectional study was to explore the prevalence ofNSis among nursing students and to find out the level of knowledge, attitude and practice regarding NSIs. About 132 of nursing students were selected randomly from four batches of nursing students at School of Health Sciences, Universiti Sains Malaysia. Data were processed using SPSS version 12.0. The data were then analyzed using descriptive statistic and Pearson Chi Square to answer the research questions. The fmdings showed that the prevalence of NSIs among nursing students was high with 4 7 incidences (35.6%). Only 34% of the incidences were reported by the students. The level of knowledge regarding NSIs among nursing student was high (M = 45.23, SD = 2.73). Level of attitude regarding NSIs was at the positive level of attitude (M = 3.91, SD = .49). Level of practice regarding NSIs was at the moderate level (M = 2.76, SD = .31 ). There were no statistically significant associations between the level of knowledge, attitude and practice with the prevalence of NSIs among the nursing students (p < .OS). Overall, this study showed that nursing students are at high risk of needle stick injury during their clinical activities. Therefore, some preventive strategies should be taken by the university and hospitals to avoid the occurrence of these problems. Nursing students also must be aware and always perform the correct nursing practice by following the guidelines of universal precaution effectively.